Pembuatan sistem pengukuran jarak benda digital berbasis sensor Fluxgate (Development of a digital object distance measurement system based on the Fluxgate sensor) - Rezy Prima; - Asrizal; - Yulkifli (PILLAR OF PHYSICS, 2013)
ABSTRACTMeasurement of the magnetic field is important because many objects have magnet and useful in life. To measure the magnetic field of an object is required a sensor. One type of sensor to detect the magnetic field is fluxgate sensor. Fluxgate magnetic sensor is a sensor that works by changing the magnetic flux around the sensor element. By utilizing the working principle of the fluxgate sensor can be madethe object distance measuring system base on digital fluxgate sensor. The purpose of this research is to determine: static characteristics of sensor fluxgate Z61, performance specifications and design specifications of the digital object distance measuring system based fluxgate sensor. Measurements of magnetic that influenced of distance from the sensor output voltage has been done. The data obtained through measurements was analyzed in two methods, those are statistics and graphs. Base on data and analysis conducted to know the sensitivity and accuracy of the fluxgate sensor Z61. Based on the data and alysisis can be presented three results. First Z61 fluxgate sensor static characteristics include transfer function of   V0=0.622x 0.0245x2+3977, sensitivity S=0.049x-0622 and accuracy 0999. The second device length is approximately 30 cm with 20 cm wide with acapacity measurement          of 7 millimeters to 15 millimeters by using a magnet as the source of the magnetic field, Z61 type fluxgate sensors, a micrometer screw and microcontroller ATMEGA 8535. Third design specifications of the digital object distance measuring system based fluxgate sensor consists of a percentage error of 12%, precision 0.875 and accuracy 0.831. Keywords: measurements system, magnetic field, fluxgate sensor